Different levels of job satisfaction by educational organization motivators - Mehrad, Aida; Hossein Tahriri Zangeneh, Mohammad (Open Science Journal, 2017)
The aim of this literature review is to recognize the important role of motivators on job satisfaction at educational organizations. The results of this study illustrate that motivators play a considerable role in changing the level of employees’ job satisfaction; additionally, they have influence on employees views and reactions. This study is focused also on job satisfaction as a main factor that improves level of organizational outcomes. Moreover, lack of attention to job satisfaction which is influenced by various motivators can reduce employees well-being as well as management in educational organization. This paper supports employees’ requirements based on different organizational motivators to attain job satisfaction at workplace.